2000
DOI: 10.1017/s0022149x00000342
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifilarial activity of extracts of the medicinal plant Cardiospermum halicacabum against Brugia pahangi

Abstract: The in vitro effects of ethanol and aqueous extracts of the medicinal plant Cardiospermum halicacabum on adult worms and microfilariae of Brugia pahangi were investigated. With or without the plant extracts in culture medium, the motility of adult worms, microfilariae and microfilarial release from female worms were monitored daily. After 7 days of culture, viability or tissue damage of adult worms was assessed using the MTT assay. At > 500 μg ml-1, the aqueous extract significantly reduced motility of adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 2 publications
1
29
0
1
Order By: Relevance
“…In addition, pharmacological evaluation of Cardiospermum halicacabum extracts showed that the plant possesses antimalarial (Waako et al, 2005), antifilarial (Khunkitti et al, 2000), antiparasitic (Boonmars et al, 2005), antipyretic (Asha & Pushpangadan, 1999), anti-inflammatory (Sadique et al, 1987), and antianxiety (Malaviya et al, 2009) activities. Also, the plant's antiulcer activity (Sheeba & Asha, 2006), and antihyperglycemic activity against streptozotocin-induced diabetes in rats as well as its antidiarrheal potentials in mice (Rao et al, 2006) are well documented in literature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pharmacological evaluation of Cardiospermum halicacabum extracts showed that the plant possesses antimalarial (Waako et al, 2005), antifilarial (Khunkitti et al, 2000), antiparasitic (Boonmars et al, 2005), antipyretic (Asha & Pushpangadan, 1999), anti-inflammatory (Sadique et al, 1987), and antianxiety (Malaviya et al, 2009) activities. Also, the plant's antiulcer activity (Sheeba & Asha, 2006), and antihyperglycemic activity against streptozotocin-induced diabetes in rats as well as its antidiarrheal potentials in mice (Rao et al, 2006) are well documented in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Among various kinds of in vitro methods, the egg hatch assays (Coles et al, 1992;Ketzis et al, 2002;Pessoa et al, 2002;Alawa et al, 2003;Hounzangbe-Adote et al, 2005) and the larval motility tests (Rabel et al, 1994;Lorimer et al, 1996;Khunkitti et al, 2000;HounzangbeAdote et al, 2005) are commonly used to test medicinal plants against nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…Different experiments showed that mature worms were injured when they were cultivated in the aqueous extracts of the plant but did not affect movement except in high concentration while ethanolic extracts in higher concentration damage both the motion of mature worms and the discharge of micro filariae from females. Though, ethanolic extract quickly decreased the movement of micro filariae while aqueous extract has gentle but proper straight macro filaricidal action on B. pahangi (Khunkitti et al, 2000).…”
Section: Antifilarial Activitymentioning
confidence: 94%